The Influence of Electric Field on the Adhesion Characteristics of the Polychloroprene-Shungite System - N. N. Komova; V. I. Solodilov; E. V. Prut; E. E. Potapov (Тонкие химические технологии, 2019)
The effect of temperature and external electric field on the adhesion characteristics in the polychloroprene-schungite system was investigated. It is shown that an increase in temperature and orientation of macromolecules of polychloroprene in an external electric field significantly increase the bond strength between the studied components. The detected effects are explained from the viewpoint of the possibility of direct chemical interaction ofshungite with polychloroprene macromolecules oriented in a certain way in the region of an adhesive compound formation. This is facilitated by the structural features of schungite (the presence of paramagnetic centers, fullerene-like structures, metal oxides) and polychloroprene in shungite, as well as by the creation of the most optimal modes for implementing this interaction. To assess the strength of the interaction between polychloroprene and the surface of shungite we used a method for determining the stress of exfoliation of a polymer film from the surface of a shungite plate. It was established that the greatest effect in strengthening the bond between polychloroprene and the surface of shungite is achieved when a polymer film is formed from a solution in carbon tetrachloride on a negative electrode (cathode). The strength of the bond between shungite and the polychloroprene film formed on the cathode is more than two times higher than this parameter when forming the same film on the anode. The energy expended during the peeling of a film formed on the cathode is twice the energy of exfoliation from the shungite plate of the film formed on the anode. The analysis of the change in the supramolecular structure of polychloroprene in the polychloroprene-shungite system as a result of the orientational influence of an external electrostatic field was carried out using the temperature dependence of the tangent of the dielectric loss angle of the systems under study. It is shown that a polychloroprene film formed in an electrostatic field has a more ordered structure compared to a similar sample formed without a field. This fact is evidenced by the shift of the maxima toward higher temperatures in the relaxation spectra of the dipole polarization for the system formed without the field, and the system formed on the cathode. The polychloroprene film containing finely dispersed shungite as a filler and formed on the cathode is characterized by an increased value of the tangent of dielectric loss angle and an increased number of peaks of dipole relaxation in the temperature range studied.